Taper model for Eucalyptus nitens, in volcanic ash soils of the region of The Araucanía (Chile) - Rodríguez-Toro, Andrés; Rubilar-Pons, Rafael; Muñoz-Sáez, Fernando; Cártes-Rodríguez, Eduardo; Acuña-Carmona, Eduardo; Cancino-Cancino, Jorge (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2016)
Generalized taper model is presented for Eucalyptus nitens (Deane & Maiden) Maiden. A non-linear model was fitted to data from 60 trees aged between 16 and 21 years, normal diameters between 11.5 and 52.0 cm, and with total heights between 47.49 and 12.27 m. Harvested in 6 stands located in 3 communes of The Araucanía region (Chile), in volcanic ash soils. The model contract with existing models in the literature, obtaining better accuracy, the least bias in each fraction high, and the higher predictive efficiency with a flexible graphical behavior and stable over the entire length of the stem. The volume function obtained from the numerical integration of the taper model predicts over 99% of the variation in stem volume without bark estimated by formula Smalian.